Epidemiological analysis regarding the incidence of Aseptic Meningitis between 2006-2012 in Brazil (Research, Society and Development, 2023)
Aseptic meningitis is defined as meningeal inflammation unrelated to an infectious process in the cerebrospinal fluid (CSF). Fever, headache, hardening of the neck, and altered mental status may be present. Despite the clear diagnostic difference, hospitalization and treatment with broad-spectrum antibiotics of children with aseptic meningitis is frequent and becomes a cause of parental stress and increased health care costs. The present study is an epidemiological, ecological, descriptive, retrospective, and quantitative study that aimed to understand the number of confirmed cases of aseptic meningitis in the state of São Paulo in the period between 2006 and 2012 and its comparison with the number of cases recorded in Brazil, correlating age and sex of the affected population. For this, data were collected through the TABNET application of the Departamento de Informática do Sistema Único de Saúde (DATASUS), which showed that, when compared with the other units of the federation, São Paulo was the state that presented the highest incidence of aseptic meningitis throughout the studied period, followed by the state of Paraná, in 2006, with 25% of the cases and ending the studied period with 6% of the total cases. A declining trend in the number of infant cases in Brazil during this period could be observed. As a perspective for the future, it is expected that new studies involving secondary data can bring a picture of greater visualization of meningitis outbreaks, with public policies implemented in the aspect of prevention and treatment.